Application of science and technology in firearm examination within the functional duties of the forensic science force in the People’s Police - Nguyen Ngoc Hoan; Nguyen Hoang Anh (Journal of State Management, 2025)
Abstract: Science and technology serve as the foundation and the key to effectively carrying out various tasks within the People’s Police forces, particularly in firearm examination. Amidst the rapid advancements of the Industrial Revolution 4.0, which is increasingly influencing all sectors, including law enforcement, application of advanced science and technology in firearm examination has become an inevitable necessity. This article focuses on analyzing and assessing the current state of science and technology applications in firearm examination as part of the functional duties assigned to the forensic science force within the People’s Police, and thereby proposes solutions to enhance the efficiency of this work in the future.